Antipathogenic Activity of Spirulina Powder - P. Santhanam, J. Sivakumar and (Recent Research in Science and Technology, 2011)
Spirulina is a microscopic blue-green alga in the shape of a spiral coil, living both in sea and fresh water. In this study, dried Spirulina was extracted at different solvents such as Hexane, Ethyl acetate, Ethanol, Butanol, Acetone, Methanol and chloroform. That extracts were stored in an airtight glass bottles in a refrigerator. Antimicrobial activity analysis from different pathogens and using well diffusion methods. Butanol extract of Spirulina also gave the highest antimicrobial activity of 19 mm against Staphylococcus epidermids, 18mm against Staphylococcus aureus and Aeromonas liquefaciens, 13mm against Candida glabrata, 12mm against Enterococcus feacalis, 11mm against Campylobacter coil and Vibrio cholerae and low activity against 5mm Salmonella typhi. Remaining solvents extracts antimicrobial activity low compare to butanol.